Membrane stability and methaemoglobin content of human erythrocytes incubated in aqueous leaf extract of Nicotiana tabacum product - P.C., Chikezie; A. R., Akuwudike; C. M., Chikezie (Free Radicals and Antioxidants)
The present study seeks to ascertain membrane stability and methaemoglobin content (%MetHb) of human erythrocytes suspended in aqueous leaf extract of N. tabacum. Erythrocyte membrane stability (%EMS) and %MetHb were measured by spectrophotometric method. Erythrocytes incubated in the five experimental concentrations of N. tabacum exhibited higher tendency to haemolyze in phosphate buffered saline solution [PBS] > 0.54 g/100 mL, whereas erythrocytes incubated in aqueous extracts of [N. tabaccum] = 0.4 and 0.8 mg/100 mL showed relatively lower level of haemolysis in [PBS] less than 0.54 g/100 mL, compared with the control samples. Experimental [N. tabacum] = 2.0 mg/100 mL caused destabilization of erythrocyte membrane by 13.3%. %MetHb of control and erythrocytes treated with aqueous extracts of N. tabacum ranged between 0.58 ± 0.09 and 1.89 ± 0.12%. Specifically, erythrocytes treated with [N. tabacum] = 0.4 mg/100 mL gave %MetHb = 0.59 ± 0.08; p less than 0.05. Experimental [N. tabacum] = 2.0 mg/100 mL engendered a paradoxical reduction in erythrocyte %MetHb = 0.58 ± 0.09; p > 0.05. The medium negative correlation (r = −0.62421) between MCF and %MetHb was an indication that N. tabacum destabilizing effect, exemplified by [N. tabacum] = 0.2 mg/100 mL; %MetHb = 0.58 ± 0.09; %EMS = −13.3, was not an oxidative process, but by mechanical perturbation by constituents of the plant extract on erythrocyte membrane structural components. Erythrocyte %MetHb in the presence of the five experimental [N. tabacum] = 0.4 − 2.0 mg/100 mL did not cause toxic methaemoglobinemia in vitro.
Keywords: Membrane stability; Methaemoglobin; N. tabacum; Erythrocytes